Paper Quilling : How it Applies to Early Childhood Fine Motor Development - Veryawan, Veryawan; Mawarni, Diva (Jurusan Pendidikan Islam Anak Usia Dini, 2025)
Fine motor skills are activities that involve small muscles in certain parts of the body and require careful coordination, although they do not require much energy. One activity that can stimulate children's fine motor development is paper quilling or the art of rolling paper. This activity is done by rolling pieces of paper using fingers or special tools, then forming rolls that are glued together so that they do not come apart easily. This Classroom Action Research was conducted at RA Al Ashriyah, located on Jalan Cut Nyak Dhien, Gampong Jawa, Langsa Kota, Langsa. The study aimed to improve children’s fine motor skills through paper quilling activities. Data collection techniques included observation of children's ability to imitate shapes, accurately paste paper forms, and cut along guided lines. A qualitative approach was used for data analysis. The findings showed that paper quilling activities were effective in improving children's fine motor development. Before the action, the percentage of indicator achievement was only 30.7%, increasing to 66.7% in cycle I, and reaching 91.7% after cycle II.